A PARAMETRIC IDENTIFICATION OF STOCHASTICALLY LOADED STRUCTURES AND ITS SOFTWARE SUPPORT (Perner's Contacts, 2011)
The paper contains descriptions of one possible approach of an identification of stochastically loaded structures. The purpose of this approach is to find an algorithm of a forecasting control of their working in real working conditions. It deals with a proposal of an application of vector time series moving average models (VARMA). Their parameters are possible to determine using the nonlinear modification of the least squares method. The paper contains a main theoretical principle of solved area and its application on a real testing structures. The main purpose of practical apllication is to identify the important parameters and to examine their relations to one another while gantry crane structure was modelled.